Liquid cooling with phase change materials for cylindrical Li-ion batteries: An experimental and numerical study. (15th January 2020) - Cao, Jiahao; Luo, Mingyun; Fang, Xiaoming; Ling, Ziye; Zhang, Zhengguo
Abstract: In this study, we design a hybrid thermal management system that combines liquid cooling and phase change materials (PCMs) for a battery pack of 20 Li-ion cylindrical cells. This system integrates a cold plate through which water flows into a PCM matrix composed of expanded graphite/RT44HC composites. The study aims at exploring factors that influence the temperature rise and the temperature uniformity of batteries. Experiments have been conducted to study the effect of water inlet temperature and flowrate, as well as the PCM content in a battery. The results show that the best control strategy would be to limit the water temperature less than 40 °C and as close to the ambient temperature. The high water flowrate reduces Tmax and ΔTplanar slightly but can significantly increase ΔTaxial and power consumption; therefore, a low flowrate is preferred. Composite PCMs with a high mass fraction of RT44HC perform better, especially under high discharge current up to 2.9C. A numerical model has also been proposed for the hybrid thermal management system to visualise temperature distribution and heat transfer routines and for system optimisation. Highlights: Experimentally test a liquid-PCM hybrid cooling system for cylindrical batteries. Separately study impacts of water and PCM on 3D battery temperature distribution. Discuss the temperature difference in a single battery and between different cells. Present a numerical model with high accuracy to guide the system design. Numerically study the effects of the thermal conductivity and latent heat.